Mineral elements in borehole water from Northern and Western geo-political zones of Nasarawa state, Nigeria - Tukura, Bitrus Wokhe; G. Igube, Ibrahimn (International Journal of Scientific World, 2016)
Mineral element contents in potable water at high concentrations may affect its quality. Concentrations of Na+, K+, Ca2+, and Mg2+ were determined in water from some boreholes in some parts of Nasarawa state, Nigeria. Levels of Na+ and K+ were determined using flame photometry, while Ca2+ and Mg2+ were quantified with the aid of atomic absorption spectrometry method. Concentrations of Ca2+ (10 – 42 mg/L) and Mg2+ (0.03 – 1.63 mg/L) were relatively low in the water samples. Nasarawa Toto (NTT) recorded the highest levels of mineral elements (0.26 – 10.61 mg/L). Mean concentrations of Na+ (7.59 – 11.08 mg/L) and Mg2+ (0.13 – 0.56 mg/L) were highest and lowest respectively. The levels of mineral elements according to studied areas varied in the order of NTT > NEG (Nasarawa Eggon) > KRV (Karu) > AKW (Akwanga) > KEF (Keffi) > GRU (Garaku). The ratios of Na/K for borehole water at Wayo (3.35) and Wamba Kurmi (3.55) at Wamba (WAM) areas were the closest to the optimal ratio of 3: 1 for the control of cardiovascular diseases, while Ca/Mg ratios were above the optimal ratio of 2:1. Total hardness levels (10 – 48 mgCaCO3/L) for water from the boreholes were < 60 mg/L, therefore, classified as being soft in nature. Mineral element concentrations in water from the boreholes were within the WHO acceptable limits for drinking water.